Glaucoma following Infant Lensectomy: 2021 Update - Walton, David S.; Yeung, Helen H. (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To review information pertaining to glaucoma following infant lensectomy surgery and to provide evidence to support the responsible mechanism of this condition.Methods and Results Described risk factors and proposed mechanisms for infantile aphakic glaucoma were assessed. The clinical evidence observed in affected glaucoma patients was analyzed, and evidence of postoperative anterior chamber fibrosis was reviewed and interpreted.Conclusion The review and assessment of laboratory and clinical evidence support the proposal that infantile aphakic glaucoma is caused, in part, by postoperative anterior chamber fibroization related to lens cell dispersion and active epithelial-mesenchymal transition with resultant filtration angle tissue injury and loss of function.
Keywords: congenital cataract; infant lensectomy; glaucoma; fibroization; EMT